Mental Fight: An Epic Poem - Okri, Ben (New York : Other Press, 2021)
"An epic poem touching on issues of racism, intolerance, and environmental destructions from Booker Prize-winning author Ben Okri. There is much to celebrate in the human journey so far--art in all its forms, advances made in the fields of technology and medicine and, for many of us, the miracle of freedom. But there is also much to regret--racism, intolerance, the destruction of our environment, the reality and the legacy of slavery. In this long, sustained consideration of the state we find ourselves in, Ben Okri invokes the past to explain the present, and sings out a message of hope. The future is still ours to make. This epic poem, an anthem for the twenty-first century, first appeared in The Times in January 1999. Its message could hardly be more relevant to our present condition. Discover this revised edition of an inspiring and extraordinarily tender work"-- Provided by publisher.
Keywords: Humanity -- Poetry; Millennium (Eschatology) -- Poetry